From Russia to Eurasia : Specific Features of the “Russosphere” from the Perspective of Business Activities of Japanese Firms - Tokunaga; Masahiro; Suganuma; Keiko; Odagiri; Nami (Russian Research Center, 2018)
In this paper we demonstrate the trends and prospects of Japanese foreign direct investment (FDI) in European Emerging Markets (EEMs) against the background of the recent development of emerging markets and explore the specificities of the Russian market the biggest EEM in terms of market size and inward FDI received. More specifically we give an overview of foreign capital flows from Japan to major EEMs and describe the achievements and problems of Japanese investors as related to business with Russia. We find that the Russian market seems to be a lucrative option for Japanese firms despite unfavorable investment conditions and limited institutional freedom afforded to outsiders including a language barrier due to the wide usage of Russian in the business field. Although use of the Russian language is one of major business obstacles affecting foreign investors making matters more challenging in the country it nonetheless provides us with a common language as a hub of business operations in the former Soviet Union countries or “Russosphere,” where Russia has still economic leverage and maintains cultural domination This research was financially supported by a Nihon University Research Subsidy (FY2014) the Kansai University Subsidy for Supporting Young Scholars (FY2015–16) the Joint Research Program of the Japan Arctic Research Network Center of Hokkaido University (FY2017) and a grant-in-aid for scientific research from the Ministry of Education Culture Sports Science & Technology of Japan (No. 17H04553: FY2017–19) 57 p.